Facile synthesis of new fused and non-fused heterocyclic systems from a γ-ketoacid - Salem, Marwa Sayed; El-Hashash, Maher Abd El-Aziz Mahmoud; Mahmoud, Al-Shimaa Omar Ali; Madkour, Hassan Mohamed Fawzy (European Journal of Chemistry, 2014)
The chemical reactivity of 4-(2-tetryl)-4-oxobut-2-enoic acid towards carbon, nitrogen, oxygen, sulfur nucleophiles and binucleophiles namely o-phenylenediamine, o-aminophenol, and o-aminothiophenol has been studied. The investigated nucleophilic reactions result in the formation of heterocyclic compounds with fused and non-fused systems namely, pyridazinone, tetrhydroquinoline, quinoxalone, oxazinone, thiazole and benzocoumarin.